DAPK and cytoskeleton-associated functions - Ivanovska, Jelena; Mahadevan, Vijayalakshmi; Schneider-Stock, Regine (Apoptosis, 2014)
Death-associated protein kinase (DAPK) undergoes activation in response to various death stimuli, and they have been associated with an increase in DAPK catalytic activity. One of the most prominent features of DAPK-induced cell death is the effect on the cytoskeleton, including loss of matrix attachment, and membrane blebbing. One known cytoskeletal-associated substrate of DAPK is the myosin-II light chain, phosphorylated by DAPK on Ser(19), thus stabilizing actin stress fibres. Moreover, paxillin, a component of focal adhesions, was found to be localized in close proximity to the tips of the DAPK-positive filaments, indicating that stress fibres containing DAPK extend to focal contacts. Forced expression of DAPK in multiple cell types results in morphological changes such as cell rounding, membrane blebbing, shrinking and detachment. During directed migration, DAPK functions as a potent inhibitor of cell polarization, as evidenced by its perturbation of the formation of static protrusion at the leading edge. Furthermore, DAPK inhibits random migration by suppressing directional persistence. One of the studies considered DAPK as an anoikis inducer. Others showed that DAP-kinase inhibits the activities of cell surface integrins by converting them into an inactive conformation. Biochemical experiments have established the DAPK binding to Syntaxin1 and its subsequent phosphorylation at Ser(188) in a Ca(2+) dependent manner. This phosphorylation event has been shown to decrease the binding of Syntaxin to MUNC18-1, a protein critically involved in synaptic vesicle docking. Here, we have investigated the structural interactions that modulate DAPK phosphorylation with Syntaxin and its functional role in binding to the MUNC18-1 to regulate vesicle docking. This review will summarize our current knowledge of the role of DAPK on cytoskeleton reorganization and report the mechanisms that regulate these changes.
EVALuna2:6622